Effectiveness of decentralizing outpatient acute malnutrition treatment with community health workers and a simplified combined protocol: a cluster randomized controlled trial in emergency settings of Mali - López-Ejeda, Noemí; Charle-Cuéllar, Pilar; Samake, Salimata; Dougnon, Abdias Ogobara; Sánchez-Martínez, Luis Javier; Samake, Mahamadou N’tji; Bagayoko, Aliou; Bunkembo, Magloire; Touré, Fanta; Vargas, Antonio; Guerrero, Saul (Frontiers in Public Health, 2024)
The outpatient treatment of acute malnutrition is usually centralized in health centers and separated into different programs according to severity of cases, which complicated case detection, care delivery, supply chain management, and made it difficult for families to access treatment. The aim of this study was to assess the impact of treating severe and moderate cases in the same program, with a simplified protocol, and decentralizing treatment outside health centers through the community health workers (CHWs).Methods: A three-armed cluster-randomized controlled trial was conducted in the Gao region (Mali), involving 1206 children between 6 and 59 months of age with noncomplicated acute malnutrition and under a non-inferiority hypothesis (5% limit). The control arm consisted of 549 children treated under the standard treatment in health centers by nursing staff. The first intervention arm consisted of 800 children treated with standard protocol, but with CHWs added as treatment providers. The second intervention arm consisted of 689 children treated by nurses and CHWs under the ComPAS simplified protocol considering mid-upper arm circumference as the sole anthropometric criterion for admission and discharge and providing a fixed dose of therapeutic food for severe and moderate cases. Coverage was assessed through cross-sectional surveys applying the SLEAC methodology for wide areas involving several service delivery units.The recovery was 76.3% in the control group, 81.8% in the group adding CHWs with the standard protocol and 93% for the group applying the simplified protocol confirming non-inferiority (5% margin). No differences were found in the time to recovery (6 weeks) nor in the anthropometric gain, while the therapeutic food expenditure was significantly lower with the simplified-combined program in severe cases (43 sachets less than control). In the moderate cases, 35 sachets of therapeutic food were used on average. With the simplified protocol, CHWs made 6% discharge errors compared to 19% with the standard protocol. Treatment coverage significantly increased with the simplifiedcombined program (SAM +42.5%, MAM +13.8%).Implementing a simplified-combined treatment program and adding CHWs as treatment providers can improve coverage while maintaining noninferior effectiveness, reducing the expenditure of nutritional intrants, and assuring the continuing care of the most vulnerable children.